محاولات تنمية مهارة الكلام عند الحبيب حسن بن أحمد بهارون بنجيل في معهد دار اللغة والدعوة باسوروان - Ardianti Binti Suharto; Farihatul Husniyah; Jihan Nabila; Fita Faila (Lahjatuna: Jurnal Pendidikan Bahasa Arab, 2021)
Habib Hasan bin Ahmad Baharun is the initiator and founder of Darul Lughah Wadda’wah Islamic Boarding School. Since his youth, he had been interested and concerned about the arabic language. His concern for the importance of the Arabic language in a muslim’s life made him eager to teach it. He made efforts to teach it at that time when a lot of Islamic boarding school founders were against it. Based on this issue, the objectives of this research are to know the ideas and efforts that have been made by Habib Hasan in teaching speaking at Darul Lughah Wadda’wah Islamic Boarding School. This research uses Qualitative Descriptive approach with the theory of the curriculum’s part. The data was collected using interviews of Habib Hasan students, the vice of the institution and his books. The data was analyzed by Miles and Huberman’s model. The results obtained by the research are that his goals of teaching speaking are for religious motivation, the materials for teaching speaking are based on modern Islamic culture, psychological issues, and grammar. The methods for teaching speaking are The Grammar-Translation Method and The Reading Method. The media for speaking are building a language environment, adding audio visual media to teaching activities, and inviting the Arabic native speakers. The teaching evaluations are use interviews and debates with students.